Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00432-018-2669-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of platinum drug use in an acute care setting: a retrospective study

Abstract: The findings suggest that platinum drugs remain one of the most commonly dispensed drugs to treat cancer patients and most patients receive a dose reduction during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
16
0
2
Order By: Relevance
“…For instance, cisplatin is a component in more active clinical trials worldwide than any other anticancer agent . Unfortunately, intrinsic and acquired resistance due to mutations remain as major obstacles for the use of platinum drugs in treating cancer. Accordingly, many new types of platinum compounds have been designed to overcome platinum resistance: trans -Pt­(II) compounds, polynuclear Pt­(II) compounds, Pt­(IV) prodrugs, , Pt­(IV) prodrugs activated by visible light, glucose–platinum conjugates, , as well as new drug delivery systems are being evaluated. , Cisplatin, carboplatin, oxaliplatin, and arsenic trioxide (As 2 O 3 ) are the only nonradioactive metal/metalloid-containing drugs approved by the FDA to treat cancer. These drugs are able to trigger apoptotic cell death, in the case of platinum compounds through direct platinum binding to nuclear DNA, , and in the case of As 2 O 3 most likely through the thiophilic As­(III) binding to cysteine rich proteins and by its ability to displace zinc from zinc-finger-containing regulatory proteins. …”
mentioning
confidence: 99%
“…For instance, cisplatin is a component in more active clinical trials worldwide than any other anticancer agent . Unfortunately, intrinsic and acquired resistance due to mutations remain as major obstacles for the use of platinum drugs in treating cancer. Accordingly, many new types of platinum compounds have been designed to overcome platinum resistance: trans -Pt­(II) compounds, polynuclear Pt­(II) compounds, Pt­(IV) prodrugs, , Pt­(IV) prodrugs activated by visible light, glucose–platinum conjugates, , as well as new drug delivery systems are being evaluated. , Cisplatin, carboplatin, oxaliplatin, and arsenic trioxide (As 2 O 3 ) are the only nonradioactive metal/metalloid-containing drugs approved by the FDA to treat cancer. These drugs are able to trigger apoptotic cell death, in the case of platinum compounds through direct platinum binding to nuclear DNA, , and in the case of As 2 O 3 most likely through the thiophilic As­(III) binding to cysteine rich proteins and by its ability to displace zinc from zinc-finger-containing regulatory proteins. …”
mentioning
confidence: 99%
“…Today, the platinum-based drugs cisplatin, carboplatin, and oxaliplatin are widely used and are among the most prominent examples of the use of metals in medicine. A recent study suggested that, in one hospital setting, approximately 50% of chemotherapeutic treatments involved a platinum anticancer drug [6,7]. Since these early discoveries, various kinds of metal-containing compounds have been investigated for their applications in therapy and diagnostics.…”
Section: Metal Complexes: Attractive Alternativesmentioning
confidence: 99%
“…For example, the cure rate of patients diagnosed with testicular cancer increased from 10 to over 95% after the introduction of cisplatin (FDA approval in 1978) [79]. At present, cisplatin and its analogues carboplatin and oxaliplatin (Fig 1) are extensively used in cancer chemotherapy, usually in combinations with other drugs [8,1012]. Indeed, 36 of 75 anticancer treatment regimens listed in Martindale drug reference book are platinum-based [13], while Pt drugs are prescribed to nearly halve of the patients undergoing chemotherapy in Australia [12].…”
Section: Introductionmentioning
confidence: 99%
“…At present, cisplatin and its analogues carboplatin and oxaliplatin (Fig 1) are extensively used in cancer chemotherapy, usually in combinations with other drugs [8,1012]. Indeed, 36 of 75 anticancer treatment regimens listed in Martindale drug reference book are platinum-based [13], while Pt drugs are prescribed to nearly halve of the patients undergoing chemotherapy in Australia [12]. Furthermore, preclinical and clinical efficacy of new anticancer drug candidates is commonly trialed in combination with platinum chemotherapeutics [11,14].…”
Section: Introductionmentioning
confidence: 99%